2023
DOI: 10.1111/opo.13093
|View full text |Cite
|
Sign up to set email alerts
|

Vergence and accommodation responses in the control of intermittent exotropia

Abstract: Purpose Individuals with different types of intermittent exotropia (IXT) may use neurally coupled accommodation and vergence responses differently from those without exotropia to achieve eye alignment. This study examined the relationship between simultaneously recorded accommodation and vergence responses in children and young adults with a range of types of IXT while aligned and deviated. Methods Responses of 29 participants with IXT (4–31 years) and 24 age‐matched controls were recorded using simultaneous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Moreover, instructions that seem simple for experienced psychophysical observers, such as “press the left arrow key when the stimulus appears to be moving left when it is in front of the screen, and the right arrow if it appears to be going the other way” might be confusing to young children and unintelligible to preverbal infants. Indeed, because infants naturally follow moving visual targets, continuous psychophysics should enable the behavioral assessment of visual function early in the developmental arc ( Mestre, Neupane, Manh, Tarczy-Hornoch, & Candy, 2023 ). Finally, if one wishes to study effects that have large individual differences, then a technique is needed in which it is possible to obtain a satisfactory amount of data from a single observer in a short amount of time so that it is, in turn, possible to collect good data from a very large number of observers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, instructions that seem simple for experienced psychophysical observers, such as “press the left arrow key when the stimulus appears to be moving left when it is in front of the screen, and the right arrow if it appears to be going the other way” might be confusing to young children and unintelligible to preverbal infants. Indeed, because infants naturally follow moving visual targets, continuous psychophysics should enable the behavioral assessment of visual function early in the developmental arc ( Mestre, Neupane, Manh, Tarczy-Hornoch, & Candy, 2023 ). Finally, if one wishes to study effects that have large individual differences, then a technique is needed in which it is possible to obtain a satisfactory amount of data from a single observer in a short amount of time so that it is, in turn, possible to collect good data from a very large number of observers.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the moderate IXT children in Group B showed slow myopic progression than the normal control in Group C. The moderate IXT children had relatively better control of exodeviation, which indicated that sufficient accommodative response compared with accommodative demand in these moderate IXT children to control normal ocular alignment. The mechanism involved in the control of IXT is still of limited understanding ( 19 ), and coupled accommodation and vergence responses are needed for compensating the additional convergence demand when overcoming the exodeviation to achieve normal alignment in IXT patients ( 20 ). The control of IXT is typically driven by neither accommodative effort alone nor convergence effort alone.…”
Section: Discussionmentioning
confidence: 99%
“…Jampolsky 23 suggested that the shift from alignment to deviation in strabismus is associated with the relaxation of fusional convergence ranges. Researchers 24,25 have shown that there is a significant correlation between the width of the fusional range and the control of exodeviation. This suggests that the ability to maintain comfortable binocular single vision is related to the strength and flexibility of FV.…”
Section: Posiɵve Fusional Vergence Break Point (δ)mentioning
confidence: 99%